Penerapan Pendidikan Orang Dewasa pada Pemberdayaan Masyarakat Tani: Studi di Kelurahan Setiawargi Kecamatan Tamansari Kota Tasikmalaya - Siti Robiah; Yus Darusman; Ahmad Hamdan (Lifelong Education Journal, 2022)
Adult education is education given to adults in accordance with the time adults have in order to foster an interest in learning on an ongoing basis throughout their lives. Empowerment of farming communities is the provision of power to the weak or powerless, especially the farming community to have knowledge, skills and competencies in agriculture, so that farmers are able to overcome the problems they face. The purpose of this study was to determine the application of adult education to empowering farming communities in the Setiawargi village. The method used in this study is a phenomenological method with a qualitative approach. Data collection techniques in this study used observation, interviews, and documentation techniques. The results show that the application of adult education has four assumptions for adult learning, including self-concept, the findings are independent and confident, experience has two components, namely personal experience and the experience of others, readiness to learn, namely material relevant to real life, orientation towards learning activities that are centered and citizen-centered learning, the need for ability, namely adults learn because they have reasons and goals, and motivation, namely internal and eksternal motivation. In practice, adult education plays an important role in shaping the personality of farmers according to their circumstances as adults. The process of empowering farming communities uses empowerment steps, namely the possibility in which there is potential development, strengthening namely knowledge and ability, protection in which there is group formation and cooperation, support, namely mentoring and support and maintenance in which there is monitoring and evaluation. The result of empowering farming communities is the creation of farmers who have the knowledge and abilities that are qualified to empower themselves and also the potential of nature. The result of the application of adult education in empowering farming communities is that farming communities learn to use adult learning assumptions to carry out the steps of the process of empowering farming communities because it is in accordance with their situation and conditions. In conclusion, with the application of adult education in empowering farming communities, farmers' productivity will increase, be able to develop their own potential and regional potential, have agricultural innovations and increase farmers' knowledge and abilities.